2015
DOI: 10.1021/ja511559d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Highly Active Fe Sites in (Ni,Fe)OOH for Electrocatalytic Water Splitting

Abstract: Highly active catalysts for the oxygen evolution reaction (OER) are required for the development of photoelectrochemical devices that generate hydrogen efficiently from water using solar energy. Here, we identify the origin of a 500-fold OER activity enhancement that can be achieved with mixed (Ni,Fe)oxyhydroxides (Ni(1-x)Fe(x)OOH) over their pure Ni and Fe parent compounds, resulting in one of the most active currently known OER catalysts in alkaline electrolyte. Operando X-ray absorption spectroscopy (XAS) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

251
2,286
13
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,232 publications
(2,554 citation statements)
references
References 73 publications
251
2,286
13
4
Order By: Relevance
“…Similarly, a volcano plot is reported, for example, among the perovskite‐structured oxides, which is correlated with the e g electron 134. Among the oxides composed of earth‐abundant materials, nickel–iron (oxy)hydroxide has been recently reconfirmed as a promising electrode in alkaline media 135, 136, 137, 138. In 2016, superior OER performance was revealed for the Ni–Co–W mixed oxyhydroxide, which requires an overpotential of only 191 mV to reach 10 mA cm −2 in 1.0 mol L −1 NaOH,139 and for Au‐supported NiCeO x , which reaches 10 mA cm −2 at an overpotential of 271 mV in 1.0 mol L −1 NaOH 140…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 87%
“…Similarly, a volcano plot is reported, for example, among the perovskite‐structured oxides, which is correlated with the e g electron 134. Among the oxides composed of earth‐abundant materials, nickel–iron (oxy)hydroxide has been recently reconfirmed as a promising electrode in alkaline media 135, 136, 137, 138. In 2016, superior OER performance was revealed for the Ni–Co–W mixed oxyhydroxide, which requires an overpotential of only 191 mV to reach 10 mA cm −2 in 1.0 mol L −1 NaOH,139 and for Au‐supported NiCeO x , which reaches 10 mA cm −2 at an overpotential of 271 mV in 1.0 mol L −1 NaOH 140…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 87%
“…The element Fe is proved to be effective for enhancing the OER activities of (oxy)hydroxides due to the enhanced structure disorder and conductivity of Fe-doping (oxy)hydroxides by previous experiment and theoretical calculation results [37,38]. This drives us to explore the influence of mole ratios of Ni/Fe in NiFe-LDH on the PEC activity of BiVO4/NiFe-LDH photoanode.…”
Section: Resultsmentioning
confidence: 96%
“…The high activity for PEC water splitting can last for over 30 h. The enhanced PEC performance is attributed to the synergistic effect of the superior charge separation efficiency facilitated by porous film and the excellent water oxidation activity resulting from NiFe-LDH nanosheet arrays OEC layer. Moreover, considering that the element Fe plays a critical role in enhancing OER active (oxy)hydroxides [37,38], the effect of Fe/Ni ratio on PEC performance of BiVO4/NiFe-LDH photoanode is discussed in detail. Furthermore, it is found that the performance of ternary NiFeCo-LDH fabricated by incorporating a certain amount of Co 2+ cation into NiFe-LDH as OEC can be further enhanced, with the photocurrent density of 4.45 mA cm −2 at 1.23 V vs. RHE, which is the highest among reported un-doped BiVO4-based photoanodes known to date.…”
Section: Introductionmentioning
confidence: 99%
“…Further increasing the potential before the onset of OER, the Ni 2+ was oxidized to Ni 3+ ; however, the Fe cations remain as Fe 3+ . In other words, the NiFe LDHs was oxidized into γ‐Ni 1− x Fe x OOH ( x < 25%) and NiFe LDH structure transformed into the Fe‐doped γ‐NiOOH structure leading to the shift for adsorption energies of oxygen intermediates 113. DFT+U calculation results further demonstrated that Fe‐doped LDHs changed the composition and structure of the oxidized catalyst 113.…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 95%
“…In other words, the NiFe LDHs was oxidized into γ‐Ni 1− x Fe x OOH ( x < 25%) and NiFe LDH structure transformed into the Fe‐doped γ‐NiOOH structure leading to the shift for adsorption energies of oxygen intermediates 113. DFT+U calculation results further demonstrated that Fe‐doped LDHs changed the composition and structure of the oxidized catalyst 113. Meanwhile, DFT+U calculation of the OER overpotential explained the reason for the enhancement OER activity of Ni 1− x Fe x OOH with the increase of Fe content.…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 99%